Rat xenograft chondrosarcoma development by human tissue fragment - Hemmati, M.; Abbaspour, A.; Alizadeh, A.M.; Khaniki, M.; Amanzadeh, A.; Mohagheghi, M.A.; Mousavi, M.S. (Experimental Oncology, 2011)
Aim: We conducted this study to develop a chondrosarcoma on rat by graft of human chondrosarcoma tumor tissue. Methods: Fourteen male Sprague-Dawley rats equally divided in xenograft-implanted and control groups. On the lateral side of the right femur distal 1/3, 5 mm incision was done on the skin after animal anesthesia. Then, was drilled 3 mm on the bone and implanted the xenograft in the bone. Radiography was taken from the operated femur weekly until the fourth week and monthly for 3 months. Four animals of each group were sacrificed after 4 weeks of operation; femur was harvested for histopathological study.